Mechano-graded electrodes mitigate the mismatch between mechanical reliability and energy density for foldable lithium-ion batteries - Ge, Xiang (2023)
Flexible lithium-ion batteries (LIBs) with high energy density are highly desirable for wearable electronics. However, difficult to achieve excellent flexibility and high energy density simultaneously via the current approaches for designing flexible LIBs. To mitigate the mismatch, mechano-graded electrodes with gradient-distributed maximum allowable strain are proposed to endow high-loading-mass slurry-coating electrodes with brilliant intrinsic flexibility without sacrificing energy density. As a proof-of-concept, the up-graded LiNi1/3 Mn1/3 Co1/3 O2 cathodes (≈15 mg cm-2 , ≈70 µm) and graphite anodes (≈8 mg cm-2 , ≈105 µm) can tolerate an extremely low bending radius of 400 and 600 µm, respectively. Finite element analysis (FEA) reveals that, compared with conventionally homogeneous electrodes, the flexibility of the up-graded electrodes is enhanced by specifically strengthening the upper layer and avoiding crack initiation. Benefiting from this, the foldable pouch cell (required bending radius of ≈600 µm) successfully realizes a remarkable figure of merit (FOM, energy density vs bending radius) of 121.3 mWh cm-3 . Moreover, the up-graded-electrodes-based pouch cells can deliver a stable power supply, even under various deformation modes, such as twisting, folding, and knotting. This work proposes new insights for harmonizing the mechanics and electrochemistry of energy storage devices to achieve high energy density under flexible extremes.